Migration and culture - Gang, Ira N.; Epstein, Gil S. (Emerald, 2010)
Culture is not new to the study of migration. It has lurked beneath the surface for some time, occasionally protruding openly into the discussion, usually under some pseudonym. The authors of the papers in this volume bring culture into the open. They are concerned with how culture manifests itself in the migration process for three groups of actors: the migrants, those remaining in the sending areas, and people already living in the recipient locations. The topics vary widely. What unites the authors is an understanding that though actors behave differently, within a group there are economically important shared beliefs (customs, values, attitudes, etc.), which we commonly referred to as culture. Culture plays a central role in our understanding of migration as an economic phenomenon. While the papers in this volume occasionally touch on this diversity and the conflicts it engenders, this is not the focus of the volume. Here the emphasis is on the distinctions in culture between migrants, the families they left behind, and the local population in the migration destination. The new interactions directly affect all three groups. Assimilation is one result; separation is also a possibility. Location choice, workplace interaction, enclave size, the opportunity for the migrant obtaining credit in their new country, the local populations reaction to migrants, the political culture of the migrants and local population, links to the country-of-origin, and the economic state of the host country, all contribute to the classic conflict between assimilation and separation. This volume will consider different aspects of the process of assimilation considering the affect on the migrants themselves, on the local population, on the families left at the home country and others.
Includes indexes.
Keywords: Emigration and immigration.; elektronické knihy; electronic books